High-cycle tensile-tensile fatigue performance of niobium alloy: Conventional vs wire-arc additive manufacturing - Tanvir, Gazi; Karim, Md Abdul; Kim, Namjung; Jeon, Yongho; Kim, Duck Bong (Journal of Materials Research and Technology, 2025)
This study explores the high-cycle fatigue (HCF) behavior of a niobium alloy, NbZr1, fabricated using wire-arc additive manufacturing (WAAM), and compares its fatigue strength to that of its powder metallurgy (PM)-produced counterpart. The analysis was conducted at three different stress levels, each characterized by a non-zero mean stress and a stress ratio of 0.1. The fatigue life under tensile-tensile fatigue loading ranged from 104 to 108 cycles for all tested samples. WAAM-produced NbZr1 exhibited a shorter average fatigue life compared to PM-NbZr1. Examination of the fracture surfaces revealed consistent fracture morphology across all loading conditions in PM-NbZr1 samples, whereas WAAM-NbZr1 samples showed varied fracture behavior. Notably, the crack propagation regions in WAAM-NbZr1 exhibited contrasting behaviors under different loading conditions. While PM-NbZr1 demonstrated typical ductile failure with elongated dimples near the final fracture region, WAAM-NbZr1 showed more pronounced cleavage crack growth, accompanied by void nucleation and coalescence along the ZrO2 particles during fatigue crack propagation. The interdendritic regions containing fine ZrO2 particles were identified as a key factor influencing crack propagation and final fracture location in WAAM-NbZr1.
Keywords: Cracks propagation; Cycle fatigue behaviors; Fatigue performance; Fatigue strength; High cycle; High cycle fatigue; Loading condition; Wire arc; Wire-arc additive manufacturing; ZrO 2; High-cycle fatigue; Niobium; Powder metallurgy; Refractory alloy; Wire-arc additive manufacturing